Graphic proposal for the great hall of the Palace of the Counts of Oliva - Luis Arciniega García (Universitat Politècnica de València, 2021)
The now-demolished Palace of the Counts of Oliva, in the province of Valencia (Spain), was an outstanding example of late Gothic and early Renaissance architecture and art. Its great hall was particularly impressive, with rich, complex decoration that constituted a cultural milestone linked recently to the ‘Germanías’, or Brotherhoods. Through research conducted in image and document collections, a graphic reproduction of the room has been produced, with special emphasis on its frieze. The procedures and techniques used in this process are examined here, before a final contemplation of the possible uses for these results.